A comparative study of geothermal pipeline route selectio methods with visual effects optimization - Sigurjón Norberg Kjærnested 1985- (2011)
The objective of this study is to develop a methodology and to create a tool for use in geothermal pipeline route selection. Special emphasis is placed on the method minimizing the visual effects of the pipeline. Two different methods for route selection are presented. In the first method, distance transform algorithms are utilized. First a method is presented to rank each point, in a digital elevation model representing the topography in question, based on visibility with regards to roads, buildings and public areas. Then a new extension to variable topography distance transform algorithms is employed to obtain the optimal path. The second method uses a non-dominated sorting genetic algorithm to obtain the optimal path with regards to first of all visual effects and pipeline length and second of all visual effects and pressure drop. This method also works with the distance transform ranking method presented in this study. A new method to generate the initial genetic algorithm population based on visual effects and pipeline length constraints is presented. The constraint‘s included in both methods are maximum allowable pipeline incline and inaccessible areas. The methods are implemented for the Hverahlíð geothermal area in Iceland. The visual effects and length of the routes recommended by the methods are compared to each other, those of the shortest possible route and the route proposed in the original planning for the geothermal area. Both the methods presented by this study are effective in obtaining pipeline routes with significantly less visual effects than conventionally designed pipeline routes. In particular the distance transform based method offers a good, functional way to design pipeline routes with regards to minimal visual impact without the route length becoming too long. Orkuveita Reykjavíkur Georg - Geothermal research group